Rapid Diagnostic Tests for Trypanosoma cruzi Infection: Field Evaluation of Two Registered Kits in a Region of Endemicity and a Region of Nonendemicity in Argentina - Lopez-Albízu, Constanza (2020)
Fil: Lopez-Albizu, Constanza. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.